Pelatihan Caregiver untuk Meningkatkan Kesiapan Perawatan Lansia Sakit Kronis di Rumah - Kartika, Annisa; Kumboyono, Kumboyono; Kristianingrum, Niko Dima; Hayati, Yati Sri (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Chronic pain in older adults causes them to experience disability which causes dependence in fulfilling daily needs (ADL). The family as a caregiver for the elderly is the main support system in the care process at home. An increase in knowledge and skills is needed by caregivers to improve their coping and reduce the burden of care. Community service activities are carried out by providing material such as the concept of chronic pain, training in care skills and accompanying home visits. Participants were families who cared for chronically ill elderly with 36 respondents. Assessment was carried out using pre-test and post-test knowledge and family readiness in caring for the elderly. The results of the assessment of family readiness to care for the elderly found that families who cared for the elderly with chronic pain had readiness in caring for the elderly (mean value = 3.91 ± 0.28), but there was data that families were not prepared to face emergency situations (mean value = 1 .63 ± 0.83). The results of caregiver training activities showed an increase in knowledge with a mean post test = 8.48 ± 1.21, an increase from the mean pre-test = 5.21 ± 1.73 and a difference in value of 3.27. The next suggestion is that there will be training that contains material on elderly care and stress management in the family so that it is able to improve the quality of care provided to the elderly.